Pengaruh Pergantian CEO Pada Profitabilitas dengan Manajemen Laba Sebagai Variabel Pemoderasi - Putri, Ni Putu Eka Kartika; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (IDX). Profitability is proxied by Return On Assets (ROA) and earnings management is calculated by the Discretionary Accrual Jones Modified. The sample selection in this study used purposive sampling and the number of sample companies taken was 32 manufacturing companies with a period of 5 years of observation, namely 2013-2017. The total sample tested was 160 samples. The analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the study it was stated that earnings management moderated the CEO turnover on the profitability of the company. The earnings management technique found in this study is income minimization which is minimizing earnings in the current year. Keywords : CEO turnover, profitability, earnings management